Telets . Taurus - Sokurov, Aleksandr (Lenfilm, 2001)
The story of Lenin's final days, his battle against his own physical decay and the understanding that his ideals never were and never will be realized. The film depicts a giant who has outlived his time - isolated in a suburban cottage away from the world waiting out his death, ineffective and forgotten. Even those that are meant to take care of him treat him as an invalid or a fool. The film has many intriguing ideas about the nature of power and the reaction of an individual faced with his own mortality,